Key Factors in Shaping Job Satisfaction: The Strategic Contribution of Transformational Leadership Dynamics and Self-Efficacy - Hijriyansyah, Mohammad; Fahmawati, Zaki Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Increasingly fierce business competition demands that companies effectively manage human resources, including maintaining employee job satisfaction. Job dissatisfaction still frequently occurs in the industrial sector and impacts increased turnover, absenteeism, decreased productivity, and disruptions to operational stability. In this context, transformational leadership and self-efficacy are two psychological factors that have the potential to increase job satisfaction. This study aims to determine the influence of transformational leadership style and self-efficacy on employee job satisfaction. The research used a quantitative method with a causal design, involving 124 employees from the production division thru a saturated sampling technique. Data was collected using job satisfaction scales, transformational leadership scales, and self-efficacy scales, and then analyzed using multiple linear regression. The research results show that the level of job satisfaction among respondents is mostly in the moderate category. Statistically, transformational leadership and self-efficacy have a positive and significant effect on job satisfaction (R² = 0.424), with the significance values for each variable being < 0.05. This finding confirms that the higher the implementation of transformational leadership and the stronger the employees' self-confidence, the higher the level of job satisfaction. The implications of this research emphasize the importance of the leader's role in creating supportive working relationships, providing motivation, and building a conducive work environment. Additionally, companies are encouraged to strengthen competency development programs to enhance employee self-efficacy in order to support the sustainability of organizational performance.Penelitian ini didasari oleh adanya permasalahan ketidakpuasan kerja yang terjadi pada perusahaan manufaktur. Ketidakpuasan kerja masih sering terjadi di sektor industri dan berdampak pada meningkatnya turnover, absensi, penurunan produktivitas, serta gangguan stabilitas operasional. Dalam konteks ini, kepemimpinan transformasional dan self-efficacy menjadi dua faktor psikologis yang berpotensi meningkatkan kepuasan kerja. Penelitian ini bertujuan untuk mengetahui pengaruh gaya kepemimpinan transformasional dan self-efficacy terhadap kepuasan kerja karyawan. Penelitian menggunakan metode kuantitatif dengan desain kausalitas, melibatkan 124 karyawan divisi produksi melalui teknik sampling jenuh. Data dikumpulkan menggunakan skala kepuasan kerja, skala kepemimpinan transformasional, dan skala self-efficacy, kemudian dianalisis menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa tingkat kepuasan kerja responden sebagian besar berada pada kategori sedang. Secara statistik, kepemimpinan transformasional dan self-efficacy berpengaruh positif dan signifikan terhadap kepuasan kerja (R² = 0,424), dengan nilai signifikansi masing-masing variabel < 0,05. Temuan ini menegaskan bahwa semakin tinggi penerapan kepemimpinan transformasional dan semakin kuat keyakinan diri karyawan, maka tingkat kepuasan kerja akan meningkat. Implikasi penelitian ini menekankan pentingnya peran pimpinan dalam menciptakan hubungan kerja yang suportif, memberi motivasi, serta membangun lingkungan kerja yang kondusif. Selain itu, perusahaan dianjurkan memperkuat program pengembangan kompetensi untuk meningkatkan self-efficacy karyawan guna mendukung keberlangsungan kinerja organisasi